An Algorithm to Optimize the Micro-Geometrical Dimensions of Scaffolds with Spherical Pores - Rodríguez-Montaño, Óscar Libardo; Cortés-Rodríguez, Carlos Julio; Uva, Antonio Emmanuele; Fiorentino, Michele; Gattullo, Michele; Manghisi, Vito Modesto; Boccaccio, Antonio (Materials, 2020)
Despite the wide use of scaffolds with spherical pores in the clinical context, no studies are reported in the literature that optimize the micro-architecture dimensions of such scaffolds to maximize the amounts of neo-formed bone. In this study, a mechanobiology-based optimization algorithm was implemented to determine the optimal geometry of scaffolds with spherical pores subjected to both compression and shear loading. We found that these scaffolds are particularly suited to bear shear loads; the amounts of bone predicted to form for this load type are, in fact, larger than those predicted in other scaffold geometries. Knowing the anthropometric characteristics of the patient, one can hypothesize the possible value of load acting on the scaffold that will be implanted and, through the proposed algorithm, determine the optimal dimensions of the scaffold that favor the formation of the largest amounts of bone. The proposed algorithm can guide and support the surgeon in the choice of a “personalized” scaffold that better suits the anthropometric characteristics of the patient, thus allowing to achieve a successful follow-up in the shortest possible time.